Levels, Sources and Potential Risks of Polychlorinated Biphenyls and Organochlorine Pesticides in Sediments of Qingduizi Bay, China: Does Developing Mariculture Matter? - Yang, Xiaolong; Wang, Lili; Zhang, Anguo; Liu, Xing; Bidegain, Gorka; Zong, Humin; Guan, Chunjiang; Song, Mingshan; Qu, Liang; Huang, Wei; Yuan, Xiutang (Frontiers in Marine Science, 2019)
Polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs), including hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs), were studied in the surface sediments of Qingduizi Bay (Yellow Sea, China). The goal was to identify whether their distribution and levels can be influenced by aquaculture activities in ponds. The total concentration of PCBs in mariculture ponds (MP) and the outer bay (OB) ranged from 0.61 ng g−1 dry weight (dw) to 2.10 ng g−1 dw and from 0.79 ng g−1 dw to 2.41 ng g−1 dw, respectively. The concentrations of hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs), ranged from 0.03 ng g−1 dw to 0.18 ng g−1 dw and from 0.24 ng g−1 dw to 31.14 ng g−1 dw, respectively. The levels of PCBs were significantly different between MP and OB, whereas no significant differences of DDTs and HCHs were detected between the two areas. Among the PCB congeners, tri-PCB and tetra-PCB were dominant, implying a historical input and atmospheric deposition for PCBs. The isomeric ratios of the compositions implicated mixture sources of new and historical inputs for HCHs. However, DDT-containing feed and pesticides in aquaculture activities could be the primary source of newly inputted DDTs. A parallel ecological risk assessment analysis showed the impact of DDTs on marine organisms. In conclusion, aquaculture in ponds influences the occurrence and distribution of persistent halogenated compounds in coastal areas, causing potential ecological impacts. This result should be a baseline for the management of aquaculture ponds regarding these compounds.